Firm heterogeneity and aggregate business services exports: Micro evidence from Belgium, France, Germany and Spain - Andrea Ariu; Elena Biewen; Sven Blank; Guillaume Gaulier; María Jesus González; Philipp Meinen; Daniel Mirza; Cesar Martín; Patry Tello (National Bank of Belgium, 2017)
This paper uses detailed micro data on service exports at the firm-destination-service level to analyse the role of firm heterogeneity in shaping aggregate service exports in Belgium, France, Germany and Spain from 2003 to 2007. We decompose the level and the growth of aggregate service exports into different trade margins paying special attention to firm heterogeneity within countries. We find that the weak export growth of France is at least partly due to poor performance by small exporters. By contrast, small exporters are the most dynamic contributors to the aggregate exports of Belgium, Germany and Spain. Our results highlight the importance of firm heterogeneity in understanding aggregate export growth.
Keywords: F14; 330; service exports; firm heterogeneity; cross-country micro data study